Thermoacoustic range verification during pencil beam delivery of a clinical plan to an abdominal imaging phantom. (June 2021) - Patch, Sarah K.; Nguyen, Chinh; Dominguez-Ramirez, Diego; Labarbe, Rudi; Janssens, Guillaume; Cammarano, Diego; Lister, Jake; Finch, Christopher; Lambert, Jamil; Pandey, Jeevan; Bennett, Christopher; Porteous, Elizabeth; et al.
Highlights: Fast (4-6 us) and stress-confined, delivery enables thermoacoustic range verification. Submillimeter range accuracy was achieved for beamlets that delivered 0.5 Gy to soft tissue. Estimates are accurate relative to ultrasound images soundspeed inhomogeneity Synchrocyclotrons deliver stress-confined proton pulses. Acoustic ringing indicated beam traversed bone; metallic implants will also cause ringing. Abstract: Purpose: The purpose of this phantom study is to demonstrate that thermoacoustic range verification could be performed clinically. Thermoacoustic emissions generated in an anatomical multimodality imaging phantom during delivery of a clinical plan are compared to simulated emissions to estimate range shifts compared to the treatment plan. Methods: A single-field 12-layer proton pencil beam scanning (PBS) treatment plan created in Pinnacle prescribing 6 Gy/fraction was delivered by a superconducting synchrocyclotron to a triple modality (CT, MRI, and US) abdominal imaging phantom. Data was acquired by four acoustic receivers rigidly affixed to a linear ultrasound array. Receivers 1–2 were located distal to the treatment volume, whereas 3–4 were lateral. Receivers' room coordinates were computed relative to the ultrasound image plane after co-registration to the planning CT volume. For each prescribed beamlet, a set of thermoacoustic emissions corresponding to varied beam energies were computed. Simulated emissions were compared to measured emissions to estimate shifts of the Bragg peak. Results: Shifts were small for high-dose beamlets that stopped in soft tissue. Signals acquired by channels 1–2 yielded shifts of - 0.2 ± 0.7 m m relative to Monte Carlo simulations for high dose spots ( 40 cGy) in the second layer. Additionally, for beam energy ≥ 125 MeV, thermoacoustic emissions qualitatively tracked lateral motion of pristine beams in a layered gelatin phantom, and time shifts induced by changing phantom layers were self-consistent within nanoseconds. Conclusions: Acoustic receivers tuned to spectra of thermoacoustic emissions may enable range verification during proton therapy.